One year of COVID-19 pandemic: Health care workers' infection rates and economical burden in medical facilities for oral and maxillofacial surgery. Issue 11 (November 2022) - Bachmann, Ella; Zellmer, Stephan; Kahn, Maria; Muzalyova, Anna; Ebigbo, Alanna; Al-Nawas, Bilal; Ziebart, Thomas; Meisgeier, Axel; Traidl-Hoffmann, Claudia; Eckstein, Fabian; Messmann, Helmut; Schlittenbauer, Tilo; et al.
Abstract: The aim of this study was to create an overview on the COVID-associated burdens faced by the oral and maxillofacial surgery (OMS) workforce during 1 year of the pandemic. OMS hospitals and private practices nationwide were surveyed regarding health care worker (HCW) screening, infection status, pre-interventional testing, personal protective equipment (PPE), and economic impact. Participants were recruited via the German Society for Oral and Maxillofacial Surgery. A total of 11 hospitals (416 employees) and 55 private practices (744 employees) participated. The HCW infection rate was significantly higher in private practices than in clinics (4.7% vs. 1.4%, p<0.01), although most infections in HCW occurred in private environment (hospitals 88.2%, private practice 66.7%). Pre-interventional testing was performed significantly less for outpatients in private practices than in hospitals (90.7% vs. 36.4%, p<0.01). Polymerase chain reaction (PCR) was used significantly more for inpatients in hospitals than in private practices (100.0% vs. 27.3%, p<0.01). FFP2/3 use rose significantly in hospitals (0% in second quarter vs. 46% in fourth quarter, p<0.05) and private practices (15% in second quarter vs. 38% in fourth quarter, p<0.01). The decrease in procedures (≤50%) was significantly higher in hospitals than in private practices (90.9% vs. 40.0%, p<0.01). Despite higher infection rates in private practices, declining procedures and revenue affected hospitals more. Future COVID-related measures must adjust the infrastructure especially for hospitals to prevent further straining of staff and finances.